A descriptive analysis of perceptions of HIV risk and worry about acquiring HIV among FEM‐PrEP participants who seroconverted in Bondo, Kenya, and Pretoria, South Africa. Issue 3 (8th September 2014) - Corneli, Amy L; McKenna, Kevin; Headley, Jennifer; Ahmed, Khatija; Odhiambo, Jacob; Skhosana, Joseph; Wang, Meng; Agot, Kawango; ,
Abstract : Introduction: Risk perception is a core construct in many behaviour change theories in public health. Individuals who believe they are at risk of acquiring an illness may be more likely to engage in behaviours to reduce that risk; those who do not feel at risk may be unlikely to engage in risk reduction behaviours. Among participants who seroconverted in two FEM‐PrEP sites – Bondo, Kenya, and Pretoria, South Africa – we explored perceived HIV risk and worry about acquiring HIV prior to HIV infection. Methods: FEM‐PrEP was a phase III clinical trial of once‐daily, oral emtricitabine and tenofovir disoproxil fumarate for HIV prevention among women in sub‐Saharan Africa. We asked all participants about their perceived HIV risk in the next four weeks, prior to HIV testing, during a quantitative face‐to‐face interview at enrolment and at quarterly follow‐up visits. Among participants who seroconverted, we calculated the frequencies of their responses from the visit conducted closest to, but before, HIV acquisition. Also among women who seroconverted, we conducted qualitative, semi‐structured interviews (SSIs) at weeks 1, 4 and 8 after participants' HIV diagnosis visit to retrospectively explore feelings of HIV worry. Applied thematic analysis was used to analyse the SSI data. Results: Among participants who seroconverted in Bondo and Pretoria, 52% reported in the quantitative interview that they had no chance of acquiring HIV in the next four weeks. We identified four processes of risk rationalization from the SSI narratives. In "protective behaviour, " participants described at least one risk reduction behaviour they used to reduce their HIV risk; these actions made them feel not vulnerable to HIV, and therefore they did not worry about acquiring the virus. In "protective reasoning, " participants considered their HIV risk but rationalized, based on certain events or beliefs, that they were not vulnerable and therefore did not worry about getting HIV. In "recognition of vulnerability, " participants described reasons for being worried about getting HIV but said no or limited action was taken to reduce their perceived vulnerability. Participants with "no rationalization or action" did not describe any HIV worry or did not engage in HIV risk reduction behaviours. Conclusions: Women who are at substantial risk of acquiring HIV may underestimate their actual risk. Yet, others who accurately understand their HIV risk may be unable to act on their concerns. Perceived HIV risk and risk rationalization are important concepts to explore in risk reduction counselling to increase the use of HIV prevention strategies among women at risk of HIV.